2022
DOI: 10.1021/acsomega.2c03174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Performance of Pyridomethene–BF2 Fluorescence Dye-Doped PVA Thin Film and PVP Nanofibers as Low γ-ray Dosimeters

Abstract: Currently, particular attention is paid to public health related to the field of γ-ray dosimetry, which is becoming increasingly important in medical diagnostic processes. Incorporating sensitive dyes as radiation dose sensors in different material hosts has shown promising radiation dosimetry application routes. In this perspective, the current study proposes a new fluorescent dye based on boron difluoride complex, the pyridomethene–BF2 named 2-(1-(difluoroboraneyl)-1,2-dihydroquinolin-2-yl)-2-(1-methylquinox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Investigation of the effect of ionizing radiation on organic dyes is of interest not only from ecological point of view (dye contamination is a major source of water pollution from textile industries [1], and irradiation is one of the most effective methods of wastewater treatment [2]), but also from the position of creating new dosimetric systems [3][4][5][6]. If in the first case the attention is paid mainly to toxic (mutagenic, carcinogenic, and so on) compounds, for example, azo [7] or anthraquinone dyes [8], then in the second, the priority goes to the dyes with pronounced optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the effect of ionizing radiation on organic dyes is of interest not only from ecological point of view (dye contamination is a major source of water pollution from textile industries [1], and irradiation is one of the most effective methods of wastewater treatment [2]), but also from the position of creating new dosimetric systems [3][4][5][6]. If in the first case the attention is paid mainly to toxic (mutagenic, carcinogenic, and so on) compounds, for example, azo [7] or anthraquinone dyes [8], then in the second, the priority goes to the dyes with pronounced optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…acetonitrile (DBDMA). DBDMA has been reported as a potential indicator for low c-ray doses [17]. Te absorption and fuorescence properties of the dye in sol-gel glass matrices were investigated and found that the photosol-gel glass matrix of the immobilized dye is the best compared to other diferent photosol-gel and organicinorganic matrices [18].…”
Section: Introductionmentioning
confidence: 99%